Social Media Roles in Spreading LGBT Movements in Malaysia - Muhammad Faiz Mokhtar; Wan Allef Elfi Danial Wan Sukeri; Zulkifli Abd Latiff (Asian Journal of Media and Communication, 2019)
This study examines how social media play roles in spreading LGBT movements in Malaysia, as well as how their potential in influencing Malaysian minds on the LGBT movements. In this study, the uses and gratifications theory applied to understand how the LGBT communities use social media as way to communicate and disseminate information in order to achieve their needs and gratifications. This study has applied qualitative approach, especially using in-depth interview and observation to the social media contents of the LGBT communities. This study finds that LGBT movements are significantly growing in Malaysia. However, due to the fact of conservative Malaysian society, the LGBT communities have optimized social media for spreading the information, sharing experiences, also communicating and engaging with another LGBT movements and communities. The use of social media comes from the nature of social media itself, namely free, open, easy and cheap access, as well as no regulatory body controls their contents. In this social media movement, the use of hashtags is very important to classify their movements, to easily communicate under certain topics, to gain new followers, as well as to maintain the current members. This study also finds that social media have played important roles in disseminating LGBT information in Malaysia, as well as in shaping the minds of Malaysians along with the spreading of LGBT movements in Malaysia.Keywords: LGBT movement; social media; uses and gratification; conservative society; social media hashtags.